Factorise 36-(4a²+12a+9)
Answers
Answered by
1
36-(4a²+12a+9)
=36-((2a)²+2.2a.3+3²)
=36-(2a+3)² [using the formula (a+b)²=a²+2ab+b²]
=(6)²-(2a+3)²
=(6+(2a+3) (6-(2a+3) [using the formula a²-b²=(a+b) (a-b)]
=(6+2a+3)(6-2a-3)
=(9+2a)(3-2a) ans
Answered by
0
Answer:
i know the answer i am solving the question on paper ,will edit the answer once i am done
Step-by-step explanation:
Similar questions
Math,
4 months ago
Math,
4 months ago
English,
9 months ago
Social Sciences,
1 year ago
Chemistry,
1 year ago